Effect of Propolis extract in Some Organic Solvents in the viability of Echinococcus granulosus protoscoleces of Sheep origin in vitro - Arqam Al Omari (College of Education for Pure Sciences, 2012)
Abstract The results of the present study revealed significant inhibitory effect of propolis extraction in organic solvents: petroleum ether, chloroform, ethyl acetate and alcohol at the concentrations of 5, 10 and 15 mg/ml in periods of 10, 15 and 20 minutes on the viability of the protoscoleces of Echinococcus granulosus of sheep origin in vitro. The concentration of 15 mg/ml of alcohol extraction of propolis inhibited the viability of protoscoleces completely 100% in 20 minutes. In general, the effects of propolis extraction in these organic solvents increased proportionally with the increase in concentration and the period of exposure. Also, the compound quercetin had been separated and diagnosed in this study from alcoholic extraction of propolis for the first time.